Work-Family Balanced and Quality of Parenting in Optimizing Children Development - Handayani, Arri; Munawar, Muniroh (Universitas Negeri Semarang, 2015)
Stimulant, which is came from their environment especially their parent is needed to maximize child growth in their golden age. A working mother whose unable to balance family and work resulting in poor parenting. This condition will influence maximal child growth. The objective of this research is to describe any supporting and inhibiting factors for child growth in particular those related to the balance of work and quality of parenting. The samples of this research are 15 working mothers. The method of the research is qualitative approach referring to naturalistic paradigm, which source is phenomenological view. This research generated descriptive data in the form of words, which are taken from observation, interview, document content, recorder. The data is about the balance of family work and the quality of parenting to maximized child growth. This research shows that a) when the mother is capable in balancing her work and family and feel satisfy for her husband assistance, the child growth will be maximal. B) when the mother is able in balancing between work and family but to tired at the cause of her role, no parenting support or colaboration of husband and wife, then the child growth will be less maximal, c) the mother should be able to balance herwork and family, but ignorance of child parenting, which make the child growth to be not maximal. For recommendation: it is suggested that the working mothers maintain the quality time to play with their children, to conduct collaborative parenting with their husband for it will have positive influence on their growth.How to citeHandayani, A., & Munawar, M. (2015). Work-Family Balanced and Quality of Parenting in Optimizing Children Development. Indonesian Journal of Early Childhood Education Studies, 4(1), 11-18. doi:10.15294/ijeces.v4i1.9447